Soaring solos : a communication campaign to increase single unwed mothers' abilities to handle parenthood problems through connection with support systems - Lim, Regene Yong Yi (Nanyang Technological University, 2022)
Soaring Solos is a non-profit communication campaign that connects single unwed mothers (SUMs) with organisations, resources, and most importantly, with each other. This is done through the creation of Singapore’s first support community exclusively for SUMs – the Soaring Solos Community. The campaign used a combination of offline engagements and online channels to reach SUMs, a group that is small and largely inaccessible. The use of the Self-Determination Theory (Ryan & Deci, 2000) and its contributing factors to an individual’s psychological wellbeing guided the campaign’s research and development, ensuring that SUMs feel increased autonomy, competence, and relatedness in their motherhood journey. The Soaring Solos Community gathered a total of 35 mothers and was successful in increasing their knowledge about the organisations and resources that they can turn to when in need of support. We did so by creating content pertinent to their informational needs while employing community building strategies to foster stronger connections between these mothers. A post-campaign evaluation of impact and output objects showed that the campaign improved their knowledge, psychological needs satisfaction, perceived benefits and interaction activity. The paper concludes with the campaign’s novelty and limitations along with future recommendations.